2013
DOI: 10.1002/ccd.24915
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of permanent pacemaker implantation following transcatheter aortic valve implantation: Analysis from the german transcatheter aortic valve interventions registry

Abstract: PPM is a common postprocedure requirement after TAVI. The absence of prior valve surgery, the implantation of Medtronic CoreValve™ prosthesis, and the presence of a porcelain aorta were independently associated with PPM after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 31 publications
2
38
0
7
Order By: Relevance
“…Our search yielded 23 studies [12][13][14]16,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] with 20 287 patients and 2553 PPM implantations published between the years 2010 and 2016 (Table). (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search yielded 23 studies [12][13][14]16,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] with 20 287 patients and 2553 PPM implantations published between the years 2010 and 2016 (Table). (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…6,41 Therefore, as the horizon of TAVR expands to include lower-risk patients, it is important to evaluate the clinical impact of this complication both in the short term and at longer durations of follow-up. 12 Dizon et al, 13 Biner et al, 14 Urena et al, 16 Baan et al, 22 D'Ancona et al, 23 De Carlo et al, 24 Houthuizen et al, 25 Buellesfeld et al, 26 Fraccaro et al, 27 Ledwoch et al, 29 Maan et al, 33 Kostopoulou et al, 34 Mouillet et al, 35 Engborg et al, 36 and Zaman et al 38 CI indicates confidence interval; MH, Mantel-Haenszel; and PPM, permanent pacemaker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of permanent pacemaker implantation in the present study is similar to that reported for this TAV device, and several recent studies have found no adverse effect of permanent pacemaker implantation after TAVI with this device on stroke or survival. 10, 11 Echocardiography core laboratory data continued to demonstrate the durability of the CoreValve bioprosthesis. No significant changes in the hemodynamic status of the implanted 26-mm/29-mm bioprostheses were seen, and the MPG and EOA remained stable from discharge to 3 years.…”
Section: Disclosuresmentioning
confidence: 99%
“…68,72,73 Several studies attempted to identify predictors of pacemaker implantation following TAVR and demonstrated that an older age, the use of the Medtronic CoreValve revalving system (ie, the incidence of pacemaker implantation in the CoreValve US Pivotal extreme risk iliofemoral study was 22%, whereas in the PARTNER Cohort B trial, in which the Edwards transcatheter heart valve [Edwards Lifesciences Inc, Irvine, CA] was implanted, it was only 3.4%), the presence of right bundle branch block, a low placement of the prosthesis, a porcelain aorta, and valve oversizing are associated with conduction disorders that required pacemaker implantation. 5,33,[74][75][76][77][78][79][80] The prognostic implications of this complication is under question as 3 studies showed no association between conduction abnormalities and prognosis and only one demonstrated increased mortality in patients who developed left bundle branch block during TAVR. [81][82][83][84] On the contrary, there is robust evidence that conduction disorders have a negative effect on LV systolic function and on patient's functional status.…”
Section: Conduction Disordersmentioning
confidence: 99%